Student-teacher relationship representation and school adjustment in primary school - Di Norcia, Anna; Cannoni, Eleonora; Bombi, Anna Silvia (Ricerche di Psicologia - Open Access, 2022)
The present study investigates student-teacher and student-peer relationships, as well as school adjustment. A novelty element is the use of drawing of oneself with a teacher to predict some aspects of children’s adjustment in primary school. Our aim was to evaluate what aspects of student-teacher relationship as perceived by children were more predictive of relational wellbeing in class and school adjustment. In sum, our results confirm that, as predicted by the attachment theory (Hamre & Pianta, 2001), a relationship perceived as close by the teacher goes hand in hand with school adjustment and relational wellbeing in school. Autonomy, too, play a positive role. In terms of predictive power, gaining autonomy from teachers seems to predict students wellbeing even more than closeness, at least as it appears from students pictorial representation.